STUDENT'S HIGHER ORDER THINKING SKILLS AS TRANSFER IN HIGH SCHOOL PHYSICS - Fathulkhair Fathulkhair; I Komang Werdhiana; Darsikin Darsikin; Nurasyah Dewi Napitupulu; Muslimin Muslimin (Universitas Negeri Medan, 2024)
The purpose of this study is to examine high school students' higher order thinking skills (HOTS) in relation to the transfer aspect in order to give a general picture of how far the transfer aspect has come, at least since it was included in the 2013 curriculum. Five questions on linear motion from the Physics subject make up the HOTS oriented research instrument. The research instrument used is a HOTS-oriented test consisting of 5 questions on linear motion from the Physics subject. The results stated that 47% of students succeeded in transferring from C1 to C4 and factual to metacognitive in question number 1. Then there were 10% of students who succeeded in transferring from C1 to C4 and factual to metacognitive in question number 2. Unfortunately, none of the students succeeded in answering questions number 3 (C4), number 4 (C5) and number 5 (C6) correctly. Students' failure to transfer their cognitive and knowledge is divided into several factors, namely lack of factual knowledge, lack of conceptual knowledge, lack of mathematical ability, not being used to using units in problem solving and not being familiar to HOTS questions.